“Chatty listeners” Listener feedback on language cultivation in Hungarian radio - Blankó, Miklós; Gyenes, Gábor (Investigationes Linguisticae, 2023)
Language cultivation is an integral part of Hungarian culture, the diversity and complexity of which cannot be compared to that of other countries. Kossuth Radio's programme Édes anyanyelvünk ‘Our Sweet Mother Tongue’ is an important forum for Hungarian language cultivation. Letters sent to the editors from the listeners comprise an instructive document of lay linguistics. In this pilot study, we processed three months' worth of letters, looking for answers to questions about who, what and how they ask, while also examining attitudes towards the mother tongue.